Independent Domination in Some Operations on Bipolar Fuzzy Graphs - Mansour Hezam AL-Shraby (IJRDO -JOURNAL OF MATHEMATICS, 2020)
In this paper, the bounds of an independent domination number in some operations on bipolar fuzzy graphs like join, Cartesian product, composition, cross product and strong product were obtained.